Correlation and regression analysis in sorghum under different levels of nitrogen - Farhood Al-salim, Salih Hadi; Saleh, Maysoun Mohamed; ALbourky, Ragheb H. A.; Abdulrahman, Abbas Lateef (Journal of Scientific Agriculture, 2017)
An experiment was conducted with sorghum varieties and different levels of nitrogen to study the correlation between traits and to study the effect of these traits on grain yield to define which traits can be considered as selection criteria for yield improvement in sorghum. A factorial irrigated field experiment was carried out in R.C.B.D. layout with three replications in Iraq, four sorghum varieties (AlKhir, Enkath, Kafir, and Rabeh) were planted under three levels of nitrogen (80,100,120) kg/h manually in 2016 at two sites. After harvest, correlation and regression analysis were studied between grain yield as the dependent variable and each of the following traits as independent variables (dry and green fodder weight, leaf area index, plant height, stem diameter, grain number and grain weight, nitrogen level). Results showed that all studied traits except grain weight were highly significantly correlated with grain yield, and about 35% of variation in grain yield could be explained by the level of nitrogen fertilizer, and also showed that plant height and dry and green fodder weight were the major contributors towards grain yield since these traits explained about (57, 52, 50)% respectively of the variation of grain yield, followed by stem diameter and grain number then leaf area index, which might be a good traits to breeders for developing high yielding cultivars in sorghum.